Mekanisme Struktur Geologi Daerah Lengkong dan Sekitarnya Kabupaten Sukabumi, Provinsi Jawa Barat - idarwati; Amarlin, Andreas Adriel (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
The Lengkong area, located in Sukabumi Regency, West Java Province, exhibits a complex geological structure. However, comprehensive studies related to structural geology in this area have not yet been conducted, thus requiring a more detailed geological understanding. The methods employed include field observations, measurement of rock layer orientations, and stereographic analysis to determine the kinematics and dynamics of deformation.The results of the study reveal the presence of three main structures: the Tegallega Anticline, the Neglasari Syncline, and the Neglasari Strike-Slip Fault. The anticline and syncline folds were formed during a compressional tectonic phase in the Plio–Pleistocene, oriented northwest–southeast, and are classified as Steeply Inclined Folds. Meanwhile, the Neglasari Fault developed during the Pleistocene as a response to northeast–southwest–oriented compressional stress, and is categorized as a Strike-Slip Dominated Fault with a Reverse Left-Slip movement type.The structural mechanisms were analyzed using the wrench fault concept, in which the folds are considered first-order structures and the faults as second-order structures. Overall, the regional north–south compressional deformation has controlled the formation of both faults and folds, while also influencing the geometry of the carbonate sandstone layers of the Lengkong Formation